Efek Rumah ikan terhadap kehadiran ikan karang - Tahapary, Jacomina; Simbolon, Domu; Wiryawan, Budy (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
The fish apartment is one of the concepts of artificial structures on the seabed where the design and construction are created to resemble the conditions of natural reefs. The fish apartment is designed with concrete material which is combined by utilizing waste pearl shells with the same construction but different in the application of the use of shells. This study was carried out for 6 months with 12 observations, which aimed to examine the treatment preferences of the fish apartment that have an impact on the presence of fish in the vicinity. The fish apartment is placed in two different locations to see the preference of the fish in the fish apartment. Data was collected using the visual census method to determine the effect of the fish apartment on the presence of fish using data analysis of variance (ANOVA) with the factorial randomized block design experimental method. The assessment of the effect of fish apartment on the presence of fish was carried out by treating the fish apartment construction itself, and other treatments that were also tested were sampling time, placement position, and repetition (groups). The types of fish observed in the fish apartment and its surroundings were 19 families on good coral reef locations, and 15 families on damaged coral reef locations. The number of fish observed was more in a fish apartment without pearl shells.